3- Modernisation and Migration: The Transformation of Labour Relations in the Global Automobile Industry - Anstey, Mark (African Sociological Review, 2006)
The need to develop and sustain competitive advantage drives businesses to constant modernisation strategies. These have a powerful influence on the shaping of labour relations systems not only in enterprises and industries, but their nations of origin. New technology and systems of work organisation oblige change in labour relations arrangements. Imperatives for growth and profitability evoke searches for new markets, and themigration of production pushing businesses into political, economic and cultural realities quite different to those of their nations of origin. In this article a brief history of the automobile manufacturing industry is presented to illustrate how forces for modernisation, market factors and migratory production strategies shape, and are shaped, by labour relations in a particular industry across nations through time. The rise of China as an automobile producing nation is likely to have profound implications for labour relations systems everywhere.